Effects of 3-nitrooxypropanol and varying concentrate feed proportions in the ration on methane emission, rumen fermentation and performance of periparturient dairy cows. Issue 2 (4th March 2021) - Schilde, Matthias; von Soosten, Dirk; Hüther, Liane; Meyer, Ulrich; Zeyner, Annette; Dänicke, Sven
ABSTRACT: The climate-relevant enteric methane (CH4 ) formation represents a loss of feed energy that is potentially meaningful for energetically undersupplied peripartal dairy cows. Higher concentrate feed proportions (CFP) are known to reduce CH4 emissions in cows. The same applies to the feed additive 3-nitrooxypropanol (3-NOP), albeit through different mechanisms. It was hypothesised that the hydrogen not utilised for CH4 formation through the inhibition by 3-NOP would be sequestered by propionate formation triggered by higher CFP so that it could thereby give rise to a synergistically reduced CH4 emission. In a 2 × 2-factorial design, low (LC) or high (HC) CFP were either tested without supplements (CONLC, CONHC ) or combined with 3-NOP (NOPLC, 48.4 mg/kg dry matter (DM); NOPHC, 51.2 mg 3-NOP/kg DM). These four rations were fed to a total of 55 Holstein cows from d 28 ante partum until d 120 post partum . DM intake (DMI) was not affected by 3-NOP but increased with CFP (CFP; p < 0.001). CH4 /DMI and CH4 /energy-corrected milk (ECM) were mitigated by 3-NOP (23% NOPLC, 33% NOPHC ) ( p < 0.001) and high CFP (12% CON, 22% 3-NOP groups) (CFP × TIME p < 0.001). Under the conditions of the present experiment, the CH4 emissions of NOPLC increased to the level of the CON groups from week 8 until the end of trial (3-NOP × CFP × TIME; p < 0.01). CO2 yield decreased by 3-NOP and high CFP (3-NOP × CFP; p < 0.001). The reduced body weight loss and feed efficiency in HC groups paralleled a more positive energy balance being most obvious in NOPHC (3-NOP × CFP; p < 0.001). ECM was lower for NOPHC compared to CONHC (3-NOP × CFP; p < 0.05), whereas LC groups did not differ. A decreased fat to protein ratio was observed in HC groups and, until week 6 post partum, in NOPLC . Milk lactose and urea increased by 3-NOP (3-NOP; p < 0.05). 3-NOP and high CFP changed rumen fermentation to a more propionic-metabolic profile (3-NOP; CFP; p < 0.01) but did not affect rumen pH. In conclusion, CH4 emission was synergistically reduced when high CFP was combined with 3-NOP while the CH4 mitigating 3-NOP effect decreased with progressing time when the supplement was added to the high-forage ration. The nature of these interactions needs to be clarified.